Emisi Gas Rumah Kaca dan Hasil Gabah dari Tiga Varietas Padi pada Lahan Sawah Tadah Hujan Bersurjan - Mulyadi, Mulyadi; Wihardjaka, A. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
The alternating dry and flooded bedding system (Surjan) optimizes land availability, by integrating food crop culture in the lower bed and annual crops in the upper bed position, of the rainfed rice field. Rainfed rice productivity is generally low, to increase its productivity rice culture should integrate the management of crop, water and nutrients. Rice field is regarded as greenhouse gas sources, especially methane (CH4) and carbon dioxide (CO2). Field experiment was conducted in the rainfed rice field in Pati, Central Java, to determine GHGs emission and grain yield from three rice varieties, applied with cattle manure, planted in the rainfed rice field, using alternating beds system. The experiment was arranged in a randomized block design with three replicates and six treatments of the combination of cattle manure application and rice varieties. The rates of cattle manure were 5 and 30 t/ha, while rice varieties were Inpari 1, Inpari 6, Ciherang. Data observed included grain yield, soil pH, fluxes of CO2 and CH4. Combination of Inpari 6 with 5 t/ha cattle manure emitted GHGs higher than combination of Inpari 6 with 30 t/ha cattle manure, while GHGs emission from combination of Ciherang with 5 t/ha cattle manure was lower than combination of Ciherang with 30 t/ha cattle manure. Variety Inpari 1 emitted the lowest GHGs, both from the combination of 5 t/ha and of 30 t/ha. The average grain yield of Inpari 1, Inpari 6, and Ciherang in the rainfed lowland rice each was 6.27, 6.01, and 5.70 t/ha, respectively. The GHGs releases from the rice variety roots depend on the availability of organic matter in the soil that is used as energy source for GHGs forming microbes.